La eficiencia de la silla vacía, como mecanismo de participación ciudadana, en el Gobierno Autónomo Descentralizado Municipal de Riobamba 2017-2019 - Katy Elizabeth, Ocaña Vallejo (2020)
ABSTRACT: In this research project, a study was carried out on: “the efficiency of the empty chair, as a mechanism for citizen participation, in the Municipal Decentralized Autonomous Government of Riobamba 2017-2019”. The right to citizen participation is established in the Constitution of the Republic of Ecuador and the laws, through the mechanisms of participation in local legislative bodies, citizens intervene with voice and vote in the Municipal Decentralized Autonomous Government of Riobamba in the sessions on a topic that is of interest for its community; The objective is to be aware on the maximum number of sessions within the Municipal Council in the periods 2017 to 2019 and the citizens are participants in public decisions, proposing ideas, requirements, promoting unity, solutions and creating a strong relationship between the state and society. The unit of analysis was located in the Municipal Decentralized Autonomous Government of Riobamba, the population involved was the Municipal Council, Council of Civil Participation and Social Control, Local Assembly, and Neighborhood Associations of Riobamba. The purpose of the research is to carry out a study in the municipality of Riobamba, the right of participation under the figure of the empty chair has several phases in terms of its knowledge and application, the lack of interest on the part of the citizens and the municipality of Riobamba when there is no a correct application of the information; in the same way, there is no department for citizen participation despite of existing a legal standard. The Municipal Council issues ordinance 008-2015, it is published inside the municipality’s website, but the citizens do not have public knowledge or do not have access to the internet. The investigation is very important in order to determine the main causes why citizen participation is not being directed so that in the future it provides a solution that materializes in: training, awareness workshops regarding the right to participate; aimed to the neighborhood leaders who are spokespersons and citizens in general.